Studies on Stability of Processing-type Genotypes of Tomato (Solanum lycopersicum L.) - H K Jyothi; M G Patil; H M Santhosha (Journal of Horticultural Sciences, 2012)
To study stability of genotypes under three diverse environments, ten genotypes along with two checks of processingtype tomato were evaluated in Randomized Block Design (RBD) with three replications. Environment included three seasons, viz., kharif (2007), rabi (2007-08) and summer (2008) to identify the most stable varieties. Overall performance of PTR-1, PTR-4, PTR-6 and 'Arka Ashish' was found stable for yield per plant, number of branches per plant, % fruit set, % acidity and lycopene content. PTR-4 and PTR-6 were stable for high yield and for good processing traits.